SERVICE CONVENIENCE UPT RUMAH SAKIT MATA MASYARAKAT JAWA TIMUR - Selly Apriyanti; Nyoman Anita Damayanti (The Indonesian Journal of Public Health, 2017)
Patient satisfaction is one of the most important thing for a hospital because  patient satisfaction is one of indicators which is assessed in hospital minimum service standards. One of the factors that can affect p atient satisfaction on a service is s ervice convenience, which means patient perception about time and effort related to purchase or use of services offered. The aim of this research was to analyze  service convenience of UPT RSMM Jawa Timur which consists of decision convenience, access convenience, transaction convenience, benefit convenience, and postbenefit convenience. This research was a descriptive research with cross sectional design. The sample was calculated by Lemeshow formula (1991), that is equal to 72 patients and taken by accidental sampling. Data were collected through questionnaires submitted through interviews. The results showed that the majority of respondents have good assessment of the decision convenience, benefit convenience, and postbenefit convenience. However, it has poor assessment of access convenience and transaction convenience. Therefore, UPT RSMM Jawa Timur needs to pay attention to access convenience and transaction convenience by maximizing the use of Electronic Data Capture machine in conducting payment transactions, adding signboard or billboard placed in strategic place to give information about location of UPT RSMM Jawa Timur, and consider to provide a home stay facility for out-of-town patients.